The Construction of Language Variations in the Television Program "Kick Andy" Episode "Dari Jongos Jadi Bos" and Its Implementation in High School Indonesian Language Learning - Ariyanto, Zahy Riswahyudha; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The aim of this research is to find out the forms of language variation found in the Kick Andy television program episode "Dari Jongos Jadi Bos", as well as their implementation in Indonesian language learning in high school. The data in this research consist of the transcripts of Andy's conversations as the host with Daniel Mananta, Julius Surja Djohan, and Jos Oren as guest stars. The data source for this research is the Kick Andy television show episode "Dari Jongos Jadi Bos". The technique used to collect data involves listening and taking notes. The results of this research found: 1. Forms of language variation in the Kick Andy television program episode “Dari Jongos Jadi Bos” include: Results of analysis of forms of language variation in the language variations in the Kick Andy television program episode “Dari Jongos Jadi Bos” include: ( 1) There are 40 language variations in terms of speakers, namely: 13 dialects, 22 chronolects, 4 acrolects and 1 vulgar form; (2) there are 19 variations of formal language consisting of 2 formal varieties, 13 informal varieties, 2 business varieties, and 2 familiar varieties; (3) there were 12 variations of language used in the field of education; and (4) language variations in terms of means, namely orally, and can be implemented in Indonesian language learning in high school, both the 2013 curriculum and the independent curriculum. Research on language variations in the Kick Andy program increases knowledge and input for Indonesian language learning in high school.